PENGARUH MOTIVASI KEWIRAUSAHAAN, BUDAYA KERJA, DAN PELATIHAN KERJA TERHADAP KINERJA PELAKU UMKM DESA GEDONGMULYO - Nikmah, Nur Laili Jaziratun; Nurhidayati, Anik (JURNAL ILMIAH EDUNOMIKA, 2025)
This study explores the effect of entrepreneurial motivation organizational culture, and skills training on the performance of micro, small, and medium enterprises (MSMEs) in Gedongmulyo Village. The analysis applies multiple linear regression methods. Data were gathered using surveys distributed to 50 MSME respondents in the area. Results reveal that entrepreneurial drive has a notable positive impact on the performance of MSME operators in Gedongmulyo Village. In contrast, organizational culture shows a significant negative (inverse) influence on their performance. Furthermore, skills training is identified as having a meaningful positive effect on MSME operators' performance. Together, entrepreneurial drive, organizational culture, and skills training explain 69% of the variability in MSME performance, with the remaining 31% attributed to other unexplored factors